Conservation of the ?Piast? cinema in Słubice: an architectural, urban or moral problem? = Kino ?Piast? w Słubicach. Problem konserwatorski, architektoniczny, urbanistyczny czy moralny? - Eckert, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For many years, attempts have been made to remove the relic of the ?Piast? Cinema in the western town of Słubice from Poland`s monuments register. This would allow for its demolition and construction of a modern commercial building on the site. The majority of the building has already be demolished, with only the front elevation remaining.
Keywords: monument; cinema building; façade of building; renovation; monuments register; art deco; cultural landscape; history; zabytki; budynek kina; fasada budynku; renowacja; rejestr zabytków; krajobraz kulturowy; historia